Color Representation in the Word ‘COVID-19’ in WHO Indonesia’s Instagram - Miftakhul Huda; Laily Rahmatika; Rani Setiawaty; Agus Budi Wahyudi; Mohammed Shamsul Hoque (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2023)
The COVID-19 pandemic in 2020 has triggered governments worldwide, including WHO Indonesia, to use social media as an essential tool for digital education dissemination. In this case, WHO Indonesia uses Instagram to share posters, with a visual emphasis through the use of color in the word 'COVID-19'. This study aims to describe how colors are represented in the word COVID-19 on WHO Indonesia's Instagram posters. This study uses qualitative research. This study was analyzed using content analysis. The results reveal that the word COVID-19 in each poster content uploaded by WHO Indonesia has a variety of colors. The color representations contained in the word COVID-19 are red as a risk warning to smokers, dark orange as sensitivity and empathy for survivors of violence, yellow-gold as a reminder of healthy activities at home, indigo as awareness of body health, teal green as maintaining physical distance, dodger blue as maintaining health during a pandemic, sienna as resilience and fortitude in facing the pandemic, white as preventing the spread of the virus, and dim gray as serious form in facing COVID-19. This study aids in comprehending the reasoning behind the selection of specific colors in the posters utilized by WHO Indonesia in their digital education endeavors regarding COVID-19. It can prove beneficial in designing more impactful health messages and understanding the influence of colors on individuals' perceptions and reactions.